FORMULASI SEDIAAN ORALLY DISINTEGRATING TABLET (ODT) ASPIRIN DENGAN SODIUM STARCH GLYCOLATE SEBAGAI SUPERDISINTEGRANT - Putri, Arine Astika; Nawangsari, Desy; Kurniasih, Khamdiyah Indah (Universitas Pekalongan, 2024)
Orally disintegrating tablets (ODT) are an alternative antiplatelet drug in the treatment of stroke which disintegrate quickly in less than 60 seconds.The research aimed to determine the effect the concentration of the sodium starch glycolate disintegrating agent on the physical properties and solubility of the aspirin (ODT) formulation and to determine the concentration of the sodium disintegrating agent glycolic starch. Aspirin ODT tablets are produced with sodium starch glycolate concentrations of 0%,10%,15% and 20%. Evaluation of ODT tablets includes weight uniformity, size uniformity, hardness, friability, tablet dissolution time and stability tests. Data were analyzed using one-way ANOVA. Results show the physical properties of tablets F1, F2, F3 and F4 including the tablet mass uniformity test showing ANOVA results (0.000), namely the test for uniformity of sizes between different diameters, the results (0.056) are no different in thickness. The difference is 0.086, the hardness test result is 0.000 so there is a difference, the friability test result is 0.125 there is a difference, and the solubility test result is 0.03 indicating there is a difference. The dissolution test produces F1(10.1%), F2(10.06%),F3(9.12%)and F4(9.3%). In the chemical stability test of the dissolution test,the dissolution percentage results experienced changes in stability on day 14, F1 (9.3%),F2(5.8%), 3 (12.6%), F4 (12.6%), stability 28 days F1(10.6%, F2(8.88%), F3(8.9%), F4(8.9%). Regarding physical stability, testing tablet weight uniformity, size uniformity, tablet hardness, friability tablets and the stability of the tablet dissolution time were obtained because the stability tests of 0.14 and 28 gave the same results.